Impact of world bank funding withdrawal on activities of women in agricultural programme of Oyo State ADP (2010)
The Agricultural Development Project (ADP) has been saddled with agricultural extension services since its inception in Oyo State in 1989. This has been through financial and technical assistance from the World Bank. However, with the withdrawal of funding assistance by the World Bank finally in 1999, the burden of financing agricultural extension services became the responsibility of the state government. This study analyzed the trend of extension activities of the Women-in-agriculture (WIA) programme of the ADP from 1989 to 1999. Areas focused were crop, livestock and fishery production. There was a downward trend of all the activities on crop right from inception of funding (excluding 1991) which was not helped by the funding withdrawal of the World Bank. The picture presented was a gloomy future for WIA in agricultural extension delivery. Also, significant differences existed in the activities (t-value of 2.504 and a p-value of 0.031) between when funding was active (1989-1995) and period of withdrawal and after (1995-2001). The study thus substantiated the importance of funding for agricultural extension activities especially as they are development oriented. It also suggested the need for governments to specifically pay attention to women farmers through intensifying funding for the WIA programmes.